EFEKTIVITAS PENGGUNAAN MEDIA FLIPBOOK INTERAKTIF TERHADAP HASIL BELAJAR KOGNITIF BAHASA INDONESIA SISWA KELAS VIII UPTD SMPN 6 SINJAI - Faqihudin; Abd. Rahman Trisno; Nurhikmah H.; Suryadi Ishak; Safaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study investigates the effectiveness of using interactive flipbook media to improve the cognitive learning outcomes of eighth-grade students in Indonesian language learning at UPTD SMPN 6 Sinjai. A quasi-experimental method was employed using a One-Group Pretest–Posttest Design involving 30 students selected purposively. Data were collected through cognitive achievement tests administered before and after the intervention. The instrument consisted of multiple-choice questions validated through expert judgment. Data analysis included descriptive statistics, a normality test (Shapiro–Wilk), and a Paired Sample t-test, followed by effect size calculation using Cohen’s d. The findings show a substantial improvement in students’ cognitive learning outcomes, with the mean pretest score increasing from 56.53 to 80.13 in the posttest, indicating a 23.6-point gain. The Paired Sample t-test revealed a significant difference between pretest and posttest scores (t = –19.87; p < 0.001). The effect size was categorized as very large (Cohen’s d = 3.628), demonstrating that the interactive flipbook had a strong influence on students’ cognitive achievement. In conclusion, interactive flipbook media is highly effective for enhancing cognitive learning outcomes in Indonesian language instruction at the junior high school level.